Can Islam Be French? : Pluralism and Pragmatism in a Secularist State - Bowen, John R. (John Richard), 1951- (Book collections on Project MUSE., 2010)
Can Islam Be French? is an anthropological examination of how Muslims are responding to the conditions of life in France. Following up on his book Why the French Don't Like Headscarves, John Bowen turns his attention away from the perspectives of French non-Muslims to focus on those of the country's Muslims themselves. Bowen asks not the usual question--how well are Muslims integrating in France?--but, rather, how do French Muslims think about Islam? In particular, Bowen examines how French Muslims are fashioning new Islamic institutions and developing new ways of reasoning and teaching. He lo.